First Yemeni coronary congenital anomaly visualized with multidetector computed tomography: Case report - Bamoshmoosh, Mohamed; Nassar, Omar; Alarhabi, Ahmed; Alarasi, Rasha; Alyashiei, Najib (Turkiye Klinikleri, 2013)
Congenital coronary artery anomalies are rare and usually lack clinical significance. There are, however, some malignant cases that may cause even myocardial infarction or sudden death. Till two decades ago, invasive coronary angiography was the gold standard procedure to study congenital coronary anomalies, although it still had important limitations. In the last years, several studies showed the usefulness of the non-invasive modalities for the detection of coronary vessel anomalies, such as magnetic resonance imaging, and especially multidetector computed tomography (MDCT). In this case report we present the first Yemeni coronary congenital anomaly visualized with MDCT. We also present a review of the literature and discuss the recent approved clinical practice guidelines.